Comparative analysis of the reconstruction of individual hip anatomy using 3 different cementless stem designs in patients with primary hip osteoarthritis - Innmann, Moritz Maximilian; Spier, Katrin; Streit, Marcus R.; Bruckner, Thomas; Gotterbarm, Tobias; Merle, Christian (The journal of arthroplasty, 2018)
Background: We questioned whether there was a radiographic difference in hip geometry reconstruction and implant fixation between 3 different cementless stem design concepts in patients with primary end-stage hip osteoarthritis. Methods: We retrospectively evaluated the preoperative and postoperative radiographs by 2 independent and blinded reviewers in a series of 264 consecutive patients who had received either a straight double-tapered stem with 3 offset options (group A), a straight double-tapered stem with 2 shape options and modular necks (group B), and a bone-preserving curved tapered stem with 4 offset options (group C). The following parameters were assessed: acetabular, femoral and hip offset (HO), center of rotation height, leg length difference (LLD), and the endosteal fit of stem in the proximal femur (canal fill index). Group comparisons were performed using a one-way analysis of variance and subsequent pairwise comparisons (t-test). Results: Postoperatively, HO could be equally restored with all 3 stem designs (P = .079). The postoperative LLD was smaller in group C compared to group A (0.8 mm [standard deviation, 3.2] vs 2.6 mm [standard deviation, 4.5], P = .002). Best combined reconstruction of HO and LLD could be achieved with the short curved stem by junior and senior surgeons (HO: −2.0 and −2.1 mm; LLD: 1.9 and 0.7 mm, respectively). The proximal and mid-height canal fill indexes were higher in groups B and C compared to group A, indicating a better metaphyseal and diaphyseal fit in the proximal femur (both P < .001). Conclusion: All 3 cementless stem designs allowed for good hip geometry reconstruction. Multiple shape and offset options allowed for a better metaphyseal stem fit and offered minor clinical advantages for leg length reconstruction. Modular necks did not provide reconstructive advantages in patients with primary hip osteoarthritis.
Online 21 November 2017
Gesehen am 05.11.2018